New encounters between arts and research - Schøllhammer, Karl Erik (Academic Quarter | Akademisk kvarter, 2016)
Discussing the work of artists like Patrício Guzman, Rosângela Rennó and Teresa Margolles this article addresses the challenges that contemporary history poses for Latin and Central American artists who articulate their engagement by means of experimental expressive specificity. An attempt will be made to redefine the borders between critical research and artistic creation and realization within the proposal of a forensic aesthetics. The article will discuss how a commitment to social and cultural content amplifies the reach of scientific engagement and stimulates its search for a performative impact through enhanced visualization and sensible materiality.